Legion life in the Roman army - Abdy, Richard Anthony (The British Museum Press, 2024)
"The Roman army has been immortalised in heroic art and screen epics, but what was life really like for an ordinary soldier? This book tells the story of everyday life in the army, including the experiences of women and enslaved people, through a range of rare objects and testimonies. These include letters from Apion and Terentianus, young Egyptian soldiers writing home to their families; the tombstone of 4-year-old Vacia, a touching reminder of the presence of children near forts; the remains of a soldier found at Herculaneum, killed in the eruption of Vesuvius in AD 79; and a board game played by soldiers in their spare time. Human experiences are set within the context of the first three centuries of the common era, widely recognised as the Roman army?s heyday. During this period, forces were split into legions of citizen-only troops and auxiliary units of non-citizen troops, with the latter offered a chance at citizenship and social advancement after around 25 years of service. As well as describing the social forces behind the army, this book addresses its violent reality for civilians and troops, battle tactics, weaponry and the risk for convicted soldiers of becoming amphitheatre entertainment are all explored. Travelling from the deserts of North Africa to the freezing climes of Scotland, and moving from the gruesome life of a medic to loving correspondence between friends, readers gain a vivid picture of life in the Roman army, with all the spectacular and ordinary experiences it involved."
Exhibition: British Museum, London, UK (01.02.2024-23.06.2024)
Keywords: Legion; Alltag; Römisches Reich; Ausstellungskatalog -- British Museum -- 01.02.2024-23.06.2024 -- London